If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7 + y) = 16 + -3y (7 * 4 + y * 4) = 16 + -3y (28 + 4y) = 16 + -3y Solving 28 + 4y = 16 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 28 + 4y + 3y = 16 + -3y + 3y Combine like terms: 4y + 3y = 7y 28 + 7y = 16 + -3y + 3y Combine like terms: -3y + 3y = 0 28 + 7y = 16 + 0 28 + 7y = 16 Add '-28' to each side of the equation. 28 + -28 + 7y = 16 + -28 Combine like terms: 28 + -28 = 0 0 + 7y = 16 + -28 7y = 16 + -28 Combine like terms: 16 + -28 = -12 7y = -12 Divide each side by '7'. y = -1.714285714 Simplifying y = -1.714285714
| 2c-c-c+3c=15 | | (100+40y+3y^2)(100+40y+3y^2)=0 | | 4+5(1+f)= | | 4x+9=x-18 | | 6t+2(4t+5)= | | 405=80n-25 | | 4.5-2k=6 | | 5+9(2+7j)= | | 6b+19=25 | | .5(16-x)=-12(x+7) | | 4x-7=4(x+5) | | X-8-1=3+4k+k | | -2x=2-(-10) | | X+.6*x=159 | | 1.72x+x=6 | | 4timesx=56 | | 3h-13=-11 | | x-1=sqrt(15-7x) | | 6=-6+48 | | 365=T+-217 | | s-15=15.53 | | 7b^2+23b+6= | | -5c-10-5c=8 | | 5(-9-4x)+10(1+10)= | | -4x-5(2x-y)-3y= | | 0.8x-11=0.34x+41 | | 2+9x=x+18 | | 3x-6+x=-25 | | 4n-40=4(n-8)+2n | | -5(-2x-13)-7x= | | 6=-6(1n-8) | | 5n+39=4(8n+3) |